Age-related brain deviations and aggression - Holz, Nathalie E.; Floris, Dorothea L.; Llera, Alberto; Aggensteiner, Pascal; Kia, Seyed Mostafa; Wolfers, Thomas; Baumeister, Sarah; Böttinger, Boris; Glennon, Jeffrey C.; Hoekstra, Pieter J.; Dietrich, Andrea; Saam, Melanie C.; et al. (Psychological medicine, 2023)
BackgroundDisruptive behavior disorders (DBD) are heterogeneous at the clinical and the biological level. Therefore, the aims were to dissect the heterogeneous neurodevelopmental deviations of the affective brain circuitry and provide an integration of these differences across modalities.MethodsWe combined two novel approaches. First, normative modeling to map deviations from the typical age-related pattern at the level of the individual of (i) activity during emotion matching and (ii) of anatomical images derived from DBD cases (n = 77) and controls (n = 52) aged 8-18 years from the EU-funded Aggressotype and MATRICS consortia. Second, linked independent component analysis to integrate subject-specific deviations from both modalities.ResultsWhile cases exhibited on average a higher activity than would be expected for their age during face processing in regions such as the amygdala when compared to controls these positive deviations were widespread at the individual level. A multimodal integration of all functional and anatomical deviations explained 23% of the variance in the clinical DBD phenotype. Most notably, the top marker, encompassing the default mode network (DMN) and subcortical regions such as the amygdala and the striatum, was related to aggression across the whole sample.ConclusionsOverall increased age-related deviations in the amygdala in DBD suggest a maturational delay, which has to be further validated in future studies. Further, the integration of individual deviation patterns from multiple imaging modalities allowed to dissect some of the heterogeneity of DBD and identified the DMN, the striatum and the amygdala as neural signatures that were associated with aggression.
Erstmals veröffentlicht: 22. April 2022
Gesehen am 01.07.2024